2020
DOI: 10.7717/peerj.9142
|View full text |Cite
|
Sign up to set email alerts
|

The combined impacts of wheat spatial position and phenology on cereal aphid abundance

Abstract: Background Wheat is a staple crop that suffers from massive yield losses caused by cereal aphids. Many factors can determine the abundance of cereal aphids and the damage they cause to plants; among them are the plant’s genetic background, as well as environmental conditions such as spatial position within the plot, the composition and the distance from neighboring vegetation. Although the effects of these factors have been under scrutiny for many years, the combined effect of both factors on aphid populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In the late stages of leaf development, when the formation of the epidermis is completed, trichomes’ functional roles become less important, and leaves often senesce and shed ( Valkama et al, 2004 ). Notably, in our recent reports, we compared the aphid resistance of wheat genotypes in a lab-controlled growth room, counting aphid reproduction after 96 h on wheat seedlings ( Batyrshina et al, 2020b ), with an evaluation of the natural aphid population on 3-month-old plants grown in the field ( Batyrshina et al, 2020a ). We found the opposite trends between the two growth conditions, where Svevo was more resistant in the lab conditions and more susceptible in the field versus the WEW accession, Zavitan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the late stages of leaf development, when the formation of the epidermis is completed, trichomes’ functional roles become less important, and leaves often senesce and shed ( Valkama et al, 2004 ). Notably, in our recent reports, we compared the aphid resistance of wheat genotypes in a lab-controlled growth room, counting aphid reproduction after 96 h on wheat seedlings ( Batyrshina et al, 2020b ), with an evaluation of the natural aphid population on 3-month-old plants grown in the field ( Batyrshina et al, 2020a ). We found the opposite trends between the two growth conditions, where Svevo was more resistant in the lab conditions and more susceptible in the field versus the WEW accession, Zavitan.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive defense mechanisms are present in plant tissues as anticipatory strategies in preparation for forthcoming adverse conditions (Mertens et al, 2021). Defense mechanisms can also be dynamic and induced upon herbivore attack, depending on plant age, developmental stage, and genetic background (Howe and Jander, 2008;Brunissen et al, 2009;Chandrasekhar et al, 2018;Batyrshina et al, 2020a). Variation in these mechanisms at the spatial level (individual parts within a plant) may be one of the key determinants of pest reproduction and feeding behavior (Awmack and Leather, 2002;Karley et al, 2002;Jakobs and Müller, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies point out that traits related to growth or to structural defenses may play an important role in driving interactions between plants and insects (Herms & Mattson 1992; Agrawal & Fischbein 2006). For instance, in a study on wheat plants, Batyrshina et al (2020) found higher numbers of aphids on fast-maturing than on slow-maturing wheat plants, and trade-offs between plant growth and defense are common in nature (Coley et al 1985; Herms & Mattson 1992). Furthermore, plants with stronger mechanical defenses tend to be better defended against insect herbivory (Caldwell, Read & Samson 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Water was provided once a week, either via rainfall or irrigation. Fertilizer was provided as previously described ( Batyrshina et al, 2020a ), and no pesticides or herbicides were applied during the experiments. The Revadim experimental site included a total of 21 accessions sown in a randomized block design with four replicates.…”
Section: Methodsmentioning
confidence: 99%